Plant Regeneration from Leaf Derived Callus of Stevia rebaudiana Bertoni - Janarthanam, B.; Gopalakrishnan, M.; Sai, G. Lakshmi; Sekar, T. (Plant Tissue Culture and Biotechnology, 2010)
Juvenile leaf explants of Stevia rebaudiana Bertoni produced maximum callus than the nodal explants cultured on MS containing 11.31 mM 2, 4-D and 2.22 mM BAP. Callus transferred to MS supplemented with 4.44 mM BA and 1.34 mM NAA showed better growth response and produced 14.0 ± 1.0 shoots with an average length of 5.6 ± 0.1 cm after 28 days. All plantlets produced profuse rooting within 25 days after transfer to half strength of MS basal medium supplemented with 2.46 mM IBA. Rooted plantlets were transferred for hardening, with 90% of plantlets successfully established in the field. Key words: Stevia rebaudiana, Leaf explant, callus culture, micropropagation D.O.I. 10.3329/ptcb.v19i2.5430 Plant Tissue Cult. & Biotech. 19(2): 133-141, 2009 (December)